Food Safety as a global public good - Herrero Olarte, Susana (2013)
The eradication of the hunger continues being today a problem to solve in spite of his devastating direct and indirect impact. Between the factors that influence in the food of the humanity, the more important are that linked to the extraordinary process of globalization that the humanity lives. It is precise to analyze if the food safety is thought from a global perspective, or if it still considered a national question.